(untitled) (Revista Lusófona de Educação, 2025)
School plays an increasingly central role in children’s development, reinforced by Physical Education, which involves the body as the main working tool, where there is continuous communication between the brain and the body, highlighting the symbiosis established between emotional, cognitive, and motor development. This study proposes a didactic approach through Physical Education, linking play and emotions, investigating the contribution of this field to children’s emotional development. The adopted methodology is qualitative in nature, with characteristics of action research (practical intervention in a real context), and was carried out at a public preschool institution located on the outskirts of Viseu. involving children between three and six years of age. It consisted of interventions focused on promoting and developing emotional skills through games. Subsequently, semi-structured interviews were conducted with the respective preschool educators. Through interaction with their group of friends, children developed the ability to control and express their emotions. The educators attributed significant importance to children’s emotional development, mentioning that it is the foundation of learning and that they continuously and transversally explore emotions, integrating them into all content areas. They recognized Physical Education’s relevance for children’s emotional development through play. They emphasized that outdoor play helps children strengthen emotional bonds with each other, promoting a healthy and collaborative learning environment. Keywords: Children; Emotional Development; Preschool Education; Physical Education.